Isolation of an N‐Heterocyclic Carbene Complex of a Borasilene. Issue 47 (26th July 2019) - Franz, Daniel; Szilvási, Tibor; Pöthig, Alexander; Inoue, Shigeyoshi
Abstract: Borasilenes, that is complexes which contain a boron–silicon double bond, have scarcely been isolated to date. In pursuit of such species, (Me3 Si)3 SiB(Cl)NHI (2, NHI=bulky N‐heterocyclic imine) was prepared and treated with KO t Bu to achieve formal extrusion of ClSiMe3 . The formation of an elusive borasilene (3int ) is postulated and it was verified by isolation of the N‐heterocyclic carbene adduct (Me3 Si)2 SiB(I Me 4 )NHI (4, I Me 4 =1, 3, 4, 5‐tetramethyl‐imidazolin‐2‐ylidene). X‐ray crystallographic study and theoretical calculations on4 diagnosed a boron–silicon double bond with marked zwitterionic character. The negative charge resides at the Si atom which marks the apex of a trigonal pyramid. Structural comparison of4 with boron cation congeners (5 +, 6 + ) suggests that the positive charge is mainly located at the trigonal planar‐coordinated B center. The conversion of4 with pinacolborane (HBpin, 2 equiv) resulted in cleavage of the double bond to produce (Me3 Si)2 Si(Bpin)2 and (NHI)BH2 (I Me 4 ). Abstract : Getting ahold of B=Si : Borasilenes, that is complexes with a boron–silicon double bond, constitute an elusive heterobimetalloidic species with only very few isolated examples known to date. The first N‐heterocyclic carbene (NHC)‐stabilized derivative of such complex is described herein and pronounced zwitterionic character is found for its B=Si bond. The positive charge resides at B and new boron cations as structural congeners are presented.